Cyclic response of FRP-confined concrete with post-peak strain softening behavior. (1st October 2016) - Li, Pengda; Wu, Yu-Fei; Gravina, Rebecca
Highlights: Cyclic behavior of FRP-confined concrete with post-peak strain softening. Test data featuring post-peak softening behavior of cyclically loaded columns. Investigation on parameters of stress-strain model under cyclic loading. Abstract: The majority of experimental studies investigating the cyclic stress-strain behavior of fiber-reinforced polymer (FRP) confined concrete feature a post-peak strain hardening. Research featuring post-peak strain softening is rare, and the development of this type of stress-strain model is currently impossible due to the lack of test results. This work addresses the gap through experimental testing and analyses of test results. Sixty FRP confined concrete cylinders were tested. Concrete strength and FRP thickness were selected as the main test variables. The test results indicated that confinement rigidity and concrete grade have a more pronounced effect on stress-strain behavior for specimens with strain softening, than those with strain hardening, in terms of the overall stress-strain curve, the unloading and reloading paths, and the plastic strain. The test results provided a database for the development of general stress-strain model that features both strain-hardening and strain-softening curves.